IMPLEMENTASI TUTORIAL KESELAMATAN KESEHATAN KERJA DALAM BENTUK APLIKASI PEMBELAJARAN BERBASISKAN ANDROID PADA PERUSAHAAN - Daniel Panjaitan; Muhammad Syahputra Novelan; Zulfahmi Syahputra (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Technological progress is something that is currently a phenomenon where one of the efforts to increase work productivity is to provide protection to workers while they are working, namely by involving workers in the Labor Social Security program and implementing a safe K3 management system for workers. This is an obligation that must be carried out by the company. The Occupational Health and Safety Management System or commonly called SMK3 is part of the overall management system which includes the organizational structure of planning, responsibilities, implementation, process procedures and resources needed for achievement development, assessment and maintenance of occupational safety and health policies in the context of controlling risks related to work activities in order to create a safe workplace. With the existence of occupational safety and health (K3) learning software, information on occupational safety and health within the scope of the company can be well known. This situation is trying to be used to make it easier for employees to understand occupational safety and health guidelines using Android-based technology smartphones.Keywords: Learning Applications, Occupational Safety and Health, Android.